1978
DOI: 10.1139/v78-483
|View full text |Cite
|
Sign up to set email alerts
|

The Raman spectra of tetrachloroantimony(V) dichloro nonafluorodiantimonate(V), tetrachloroantimony(V) undecafluoroantimonate(V), and related molecules

Abstract: The Raman spectra of [SbCl4+][Sb2Cl2F9−], [SbCl4+][Sb2F11−], [AsCl4+][SbF6−], and SbCl4F(NbF5)x are reported. The spectra of all compounds except the last are interpreted in terms of a tetrahedral cation with weak association between the cation and anion. The spectra of the adduct found between SbCl4F and NbF5 are interpreted in terms of polymeric fluorine bridged arrangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

1979
1979
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
1
4
0
1
Order By: Relevance
“…The Sb−Cl stretching and Cl−Sb−Cl bending modes of the mixed Cl/OTeF 5 antimony(V) anions have not been explicitly assigned, but bands that compare favorably with their counterparts in the SbCl 4 - and SbCl 6 - anions 54 are indicated in Table (also see sections on syntheses and NMR spectra). The assignments of the AsCl 4 + and AsBr 4 + cation vibrations were made by comparison with the vibrational spectra of [AsX 4 ][AsF 6 ] (X = Cl, Br), ,, [AsCl 4 ][SbF 6 ], [AsCl 4 ][MCl 4 ] (M = Al, Ga), and [AsBr 4 ][Al 2 Br 7 ] 43 and were confirmed by theoretical calculations (see Computational Results and Table ). Splittings arising from the 35/37 Cl isotope effect, which were not reported in previous studies, were, however, observed on ν 1 (A 1 ) and ν 3 (T 2 ) of the AsCl 4 + cation for both the As(OTeF 5 ) 6 - and Sb(OTeF 5 ) 6 - n Cl n - salts, although they were better resolved in the latter case.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The Sb−Cl stretching and Cl−Sb−Cl bending modes of the mixed Cl/OTeF 5 antimony(V) anions have not been explicitly assigned, but bands that compare favorably with their counterparts in the SbCl 4 - and SbCl 6 - anions 54 are indicated in Table (also see sections on syntheses and NMR spectra). The assignments of the AsCl 4 + and AsBr 4 + cation vibrations were made by comparison with the vibrational spectra of [AsX 4 ][AsF 6 ] (X = Cl, Br), ,, [AsCl 4 ][SbF 6 ], [AsCl 4 ][MCl 4 ] (M = Al, Ga), and [AsBr 4 ][Al 2 Br 7 ] 43 and were confirmed by theoretical calculations (see Computational Results and Table ). Splittings arising from the 35/37 Cl isotope effect, which were not reported in previous studies, were, however, observed on ν 1 (A 1 ) and ν 3 (T 2 ) of the AsCl 4 + cation for both the As(OTeF 5 ) 6 - and Sb(OTeF 5 ) 6 - n Cl n - salts, although they were better resolved in the latter case.…”
Section: Resultsmentioning
confidence: 80%
“…All members of the AsX 4 + (X = F, Cl, Br, I) series have been synthesized and characterized by Raman spectroscopy, and AsF 4 + 44 and AsCl 4 + 36 have also been characterized by infrared spectroscopy. The salts of AsF 4 + and AsCl 4 + , namely, [AsF 4 ][PtF 6 ], [AsCl 4 ][SbCl 6 ]·AsCl 3 , [AsCl 4 ][AsF 6 ], ,, [AsCl 4 ][AlCl 4 ], and [AsCl 4 ][GaCl 4 ] 35,40 are stable compounds, but only [AsCl 4 ][SbCl 6 ]·AsCl 3 45 and [AsCl 4 ][AsF 6 ] 46,47 have been structurally characterized by single-crystal X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…The identity of both compounds was confirmed by elemental analysis. The 1 H and 13 C NMR as well as the 31 …”
Section: Resultsmentioning
confidence: 99%
“…Materials and Apparatus . Activated NaN 3 , [AsCl 4 ][AsF 6 ], [Me 4 N][AsCl 4 ], As(N 3 ) 5 ·py, [SbCl 4 ][Sb 2 F 11 ], [Ph 4 P][SbCl 4 ], and [Et 4 N][SbCl 6 ] were prepared by literature methods. A solution of HN 3 in CH 2 Cl 2 was prepared by a modified literature method …”
Section: Methodsmentioning
confidence: 99%
“…[9] Im Laufe von drei Tagen werden die Banden von [ClCO] immer schwächer. Aus der Suspension entsteht eine klare Flüssigkeit, und es bildet sich unter anderem [SbCl 4 ] (444, 392, 140, 125 cm À1 ), [17,18] was auf einen Cl/F-Austausch schlieûen läût. Im IR-Spektrum der überstehenden Gasphase lassen sich COFCl, COF 2 sowie auch etwas CF 4 und CO 2 nachweisen.…”
unclassified